Historical evolution of dentristry in Las Tunas City - Yadira Rodríguez González; Maydelyn Ureña Espinosa; Onnia Almaguer Labrada (Editorial Ciencias Médicas, 2018)
Introduction: the history of dentistry is a necessary tool to understand the essence of the profession. Objective: analyze the historical evolution of dentistry in the province of Las Tunas. Methods: a historical study was conducted from September 2010 to July 2017. The primary sources of information were texts and historical documents consulted at the Provincial Library, the Provincial Historical Archive and the City Historian's Office, as well as interviews with dentists and their relatives. The materials consulted included 3 books, 2 journal papers and 12 documents from the Provincial Historical Archive. Results: in the years preceding the Revolution, there were only 16 dental surgeons in the province. Dental services were ill-equipped and limited to tooth extractions and emergencies. At present 47 dental care facilities are available to the population, and 1 706 professionals and technicians have been trained. Final considerations: the dental profession in the territory has developed considerably, improving the quality of life of the population and their satisfaction.